2021
DOI: 10.3389/fbioe.2021.709679
|View full text |Cite|
|
Sign up to set email alerts
|

The Fabrication of a Gellan Gum-Based Hydrogel Loaded With Magnesium Ions for the Synergistic Promotion of Skin Wound Healing

Abstract: To accelerate serious skin burn wound healing in a convenient manner, an interpenetrating network of hydrogel consisting of gellan gum and polyacrylamide was synthesized by chemical crosslinking and Mg2+ ion immersion techniques. The prepared Mg2+@PAM/GG hydrogel was characterized by morphology, water vapor loss, swelling ratio, rheological properties, tensile mechanical, biocompatibility, and flow cytometry study. The results show that Mg2+@PAM/GG hydrogel’s mechanical strength could be enhanced by the dual n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…Together, these results clearly demonstrated that the desirable physicochemical characteristics endowed the PDA-PAM/Mg 2+ hydrogel the best wound healing efficiency. Compared with another Mg 2+ -based hydrogel (21 days) composing of PAM and Gellan Gum (GG), our PDA-PAM/Mg 2+ gel (14 days) still showed a shorter healing time [ 39 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Together, these results clearly demonstrated that the desirable physicochemical characteristics endowed the PDA-PAM/Mg 2+ hydrogel the best wound healing efficiency. Compared with another Mg 2+ -based hydrogel (21 days) composing of PAM and Gellan Gum (GG), our PDA-PAM/Mg 2+ gel (14 days) still showed a shorter healing time [ 39 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…These hydrogels displayed increased tension strength from 86 to 392 kPa and elongation at break from 84 to 231% compared with plain gellan gum hydrogels, indicating good mechanical performance that is significant for wound dressing. The in vivo experiments using the rat full-thickness burn model showed that the gellan gum/polyacrylamide hybrid hydrogels incorporated with magnesium ions significantly accelerated wound closure in the case of the sustained release of magnesium ions in the wound beds [ 72 ]. Ozkahraman et al designed gellan gum-based bilayer hydrogels loaded with an antibiotic, ampicillin.…”
Section: Gellan Gum-based Wound Dressingsmentioning
confidence: 99%
“…Globally, the obtained results open prospective for the application of photocurable GG derivatives for the fabrication of nanocomposite films with antibacterial properties. GG is only marginally considered in the scenario of the wound dressing materials [39], even if it possesses interesting features to efficiently support wound healing [54][55][56][57].…”
Section: Antimicrobial Activity In Liquid Culture Mediamentioning
confidence: 99%